Mathematics for Economics and Business (5th Edition) - Jacques, Ian (FT Times, 2012)
Mathematics for Economics and Business provides a thorough foundation in mathematical methods for economics, business studies and accountancy students. Assuming little prior knowledge, this informal text is a great companion for those who have not studied maths in depth before. This book truly promotes self-study as students are encouraged to tackle problems as they go along and can see fully worked examples to help their understanding. Both beginners and more advanced students will find material in this book relevant to their needs.